Precursor‐Directed Nucleation and Self‐Assembly Growth: From Hollow Microprisms to Nanoplatelets. Issue 5 (22nd March 2017) - Li, Zhaojin; Hu, Tao; Peng, Zhenzhen; Hu, Minmin; Zhu, Kongjun; Wang, Xiaohui
Abstract: Directly controlling the morphology and orientation of nanocrystals is a key step for their tailored applications. Achieving such controlled synthesis requires insight into the formation mechanism. Using Li3 PO4 microprisms as a solid precursor sealed in capillary tube, we unravel the structural and morphological evolution from the precursor to the resultant LiFePO4 nanoplatelets by means of in situ temperature monitoring, ex situ Raman spectroscopy and TEM/STEM. Under water‐deficient conditions, the precursor dissolves in a sluggish manner, facilitating simultaneous heterogeneous nucleation of LiFePO4 on undissolved Li3 PO4 and homogeneous nucleation in solution. Vertically aligned nanoribbons consisting of primary LiFePO4 particles on the Li3 PO4 surface undergo self‐assembly growth though oriented attachment. The [100]‐orientation is explained by the fact that H3 O + preferably adsorbed on the LiFePO4 (100) facet and suppressed the crystal growth more along the [100] direction than the others. Abstract : Using hollow‐prismatic Li3 PO4 microcrystals as a solid precursor and 'tracer', the structural and morphological evolution from microprisms to [100]‐oriented LiFePO4 ultrathin nanoplatelets is visualized.